2021
DOI: 10.1021/acsabm.1c00961
|View full text |Cite
|
Sign up to set email alerts
|

Improved Photophysical Properties of Ionic Material-Based Combination Chemo/PDT Nanomedicine

Abstract: Herein, a cost-effective and prompt approach to develop ionic material-based combination nanodrugs for cancer therapy is presented. A chemotherapeutic (phosphonium) cation and photodynamic therapeutic (porphyrin) anion are combined using a single step ion exchange reaction. Afterward, a nanomedicine is prepared from this ionic materials-based combination drug using a simplistic strategy of reprecipitation. Improved photophysical characteristics such as a slower nonradiative rate constant, an enhanced phosphore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…[P 66614 ]Cl is known to induce cytotoxic effect towards cancerous cells. 29 This study can answer if the replacement of small chloride ion of the chemotherapy molecule, [P 66614 ]Cl with NIR dye alters its chemotherapeutic effect. Since the parent [P 66614 ]Cl chemotherapy molecule is used in the liquid form while the hydrophobic chemo-PTT molecules are used as NPs in the cell media, the dark cytotoxicity of the drug should be affected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[P 66614 ]Cl is known to induce cytotoxic effect towards cancerous cells. 29 This study can answer if the replacement of small chloride ion of the chemotherapy molecule, [P 66614 ]Cl with NIR dye alters its chemotherapeutic effect. Since the parent [P 66614 ]Cl chemotherapy molecule is used in the liquid form while the hydrophobic chemo-PTT molecules are used as NPs in the cell media, the dark cytotoxicity of the drug should be affected.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that INMs can show enhanced toxicity compared to their parent drugs. 28,29,46 Therefore, cellular dark toxicity of the parent PTAs and chemo-PTT INMs was analyzed in two different cell lines (cancerous breast from mouse and human) to inspect potential selectivity of the combination INMs in regard to species. Two cell lines are used since the phosphonium based chemotherapeutic cation is known to exhibit different toxicity in various cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once dissolved in an aqueous solution, the absorption spectra of the porphyrins C5SHU, C6SHU, and C7SHU in water was compared to that of the solvated porphyrin recorded in polar organic solvent DMSO and the porphyrin forced to stack in 1 M HCl ( Figure 1 ). The spectra of C5SHU in water has a sharp Soret band like that of the solvated C5SHU in recorded DMSO, the spectra of C6SHU and C7SHU in water have Soret bands that are broader than those recorded in DMSO spectra but not as the broad Soret bands seen in the stacked porphyrins [ 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…13). 168 This chemotherapeutic and photodynamic therapeutic (chemo-PDT) IMs was a hydrophobic compound, which would easily be converted to INMs in aqueous/buffer solution via reprecipitation. 169,170 [P 66614 ][IR783] INMs showed better photothermal conversion efficiency than the parent dye.…”
Section: Ionic Materialsmentioning
confidence: 99%